2016
DOI: 10.1093/pcp/pcw083
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of PsbS Function and Stomatal Conductance to Foliar Temperature in Higher Plants

Abstract: Natural capacity has evolved in higher plants to absorb and harness excessive light energy. In basic models, the majority of absorbed photon energy is radiated back as fluorescence and heat. For years the proton sensor protein PsbS was considered to play a critical role in non-photochemical quenching (NPQ) of light absorbed by PSII antennae and in its dissipation as heat. However, the significance of PsbS in regulating heat emission from a whole leaf has never been verified before by direct measurement of foli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 82 publications
2
19
0
Order By: Relevance
“…Increased susceptibility to HL and UV‐AB can be a consequence of impaired non‐photochemical quenching (NPQ), which is responsible for the dissipation of excess light energy as heat (Kulasek et al ., 2016; Białasek et al ., 2017). Thus, we monitored NPQ using chlorophyll a fluorescence in Col‐0, cia2–2 , cil‐1 , cil‐2 , cia2–2 cil‐1 and cia2–2 cil‐2 (Figures 6 and S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased susceptibility to HL and UV‐AB can be a consequence of impaired non‐photochemical quenching (NPQ), which is responsible for the dissipation of excess light energy as heat (Kulasek et al ., 2016; Białasek et al ., 2017). Thus, we monitored NPQ using chlorophyll a fluorescence in Col‐0, cia2–2 , cil‐1 , cil‐2 , cia2–2 cil‐1 and cia2–2 cil‐2 (Figures 6 and S4).…”
Section: Resultsmentioning
confidence: 99%
“…The redox state of the PQ pool and H 2 O 2 are also involved in high light acclimatory responses (Karpiński et al ., 1999; Mühlenbock et al ., 2008; Gilroy et al ., 2016). Experimentally, it is almost impossible to separate foliar heat shock from high light responses, because exposure to high light for a few seconds significantly warms up Arabidopsis leaves due to the dissipation of energy as heat (Kulasek et al ., 2016). Therefore, it is interesting that CIA2 and CIL antagonistically influence high light and UV‐B acclimation versus thermotolerance in ambient light.…”
Section: Discussionmentioning
confidence: 99%
“…DCMU binds to the quinone B- (Q B ) binding pocket and blocks the oxidation of quinone A (Q A ) and subsequent reduction of plastoquinone (PQ). It results in a disturbance in F m and F 0 , which leads to strong reduction of NPQ ( Escoubas et al 1995 , Kulasek et al 2016 ). In our experiments, DCMU application also resulted in a strong decrease of NPQ in the leaf area exposed to this inhibitor; however, it did not disturb spreading of Chl fluorescence changes across the treated region ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, however, we found no direct correlations between PsbS levels and foliar temperature responses in leaves exposed to strongly increasing and decreasing short (30 s) episodes of excess light. We concluded that PsbS is not directly involved in the regulation of foliar temperature dynamics under variable light conditions, although it still could be indirectly involved in the regulation of stomatal conductance and the transpiration rate and, thus, of foliar temperature (Kulasek, Bernacki, Ciszak, Wito n, & Karpi nski, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Recently, however, we found no direct correlations between PsbS levels and foliar temperature responses in leaves exposed to strongly increasing and decreasing short (30 s) episodes of excess light. We concluded that PsbS is not directly involved in the regulation of foliar temperature dynamics under variable light conditions, although it still could be indirectly involved in the regulation of stomatal conductance and the transpiration rate and, thus, of foliar temperature (Kulasek, Bernacki, Ciszak, Witoń, & Karpiński, ). Szechyńska‐Hebda, Kruk, Górecka, Karpińska, and Karpiński () demonstrated that the local and systemic acquired acclimation (SAA) (Karpiński et al, ) – light acclimatory responses induced by episodes of excess light – are regulated by electrical signalling and are required for local and systemic NPQ adjustments (Białasek, Górecka, Mittler, & Karpiński, ).…”
Section: Introductionmentioning
confidence: 98%